Conscription hurts: The effects of military service on physical health, drinking, and smoking - Dirk Bethmann; Jae Il Cho (Elsevier, 2023)
Almost all South Korean men serve in the country's armed forces for two years. In this paper, we investigate whether the military service affects the health of draftees. Using an event study design, we use the conscription years to identify the effect the military service has on soldiers' physical health as well as on their smoking and drinking behavior. Our results show that the compulsory military service has a strong and long-lasting negative effect on physical health. Moreover, people who are drafted into the armed forces are more likely to consume more alcohol and cigarettes even years after they are discharged. Our results are of great interest to decision-makers weighing the pros and cons of conscription armies: mandatory military service adversely affects the male labor force and exacerbates drinking and smoking behavior.